2010
DOI: 10.1007/s11270-010-0519-5
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Atmospheric Nitrogen Deposition Effects Upon the Nitrate Concentration of Stream Waters in a Forested Mountain Area

Abstract: Nitrogen compounds generated by anthropogenic combustion deposits in forest watersheds and induce nitrogen saturation of the area. Because excess nitrogen is derived from atmospheric deposition, this action is expected to uniformly affect a wide area of forest soils. Geographically, heterogeneous nitrate concentration of stream water within a small area has been attributed to the tree type, geological setting and tree cut. In this article, we hypothesized that the effect of the atmospheric nitrogen deposition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…In the present study, about 25% of samples were greater than 1 mg-N L −1 as , which was a larger distribution ratio than that in Japan-wide monitoring 25 . Such high N concentration samples in the study region are comparable with values in European forest 17 , 18 and the same Kanto-region forest catchment reported to have N-saturated forests 25 27 . However, contrary to the European forests, pH in 99% of samples were >6.5, suggesting streams without acidification despite relatively high acid deposition loadings.…”
Section: Resultssupporting
confidence: 85%
“…In the present study, about 25% of samples were greater than 1 mg-N L −1 as , which was a larger distribution ratio than that in Japan-wide monitoring 25 . Such high N concentration samples in the study region are comparable with values in European forest 17 , 18 and the same Kanto-region forest catchment reported to have N-saturated forests 25 27 . However, contrary to the European forests, pH in 99% of samples were >6.5, suggesting streams without acidification despite relatively high acid deposition loadings.…”
Section: Resultssupporting
confidence: 85%
“…S2 ), including one tropical and four subtropical sites in southwestern China; nine temperate sites in central, southern, and western Japan; and four Arctic tundra sites in northern Alaska. Among them, Tsukuba Forest Experimental Watershed (TKB) and Tama-Kyuryo Field Museum upper slope (TMU) and lower slope (TML) ( SI Appendix , Table S1 ) are characterized by high soil NO 3 − or N saturation ( 49 , 64 , 65 ), while the Arctic sites TFS, Sagavanirktok River Valley (SAG), and IMT ( SI Appendix , Table S1 ) are characterized by unmeasurable nitrification rates and negligible soil NO 3 − and, thus, are assumed to be typically low-NO 3 − ecosystems ( SI Appendix , Fig. S2 ).…”
Section: Methodsmentioning
confidence: 99%
“…As the growing season coincides with the rainy season in Japan, greater nitrate export observed during this season likely reflects the combined influence of increased microbial nitrate production and high water drainage [ Mitchell et al ., ; Mitchell , ]. In a study of forested catchments near Tokyo, Tabayashi and Koba [] reported higher stream nitrate concentrations and δ 18 O‐ NO3 values in areas receiving elevated N deposition inputs. However, maximum δ 18 O‐ NO3 values only reached +6‰, showing that nitrification sources dominated stream nitrate even in catchments with high stream nitrate concentrations.…”
Section: Major Drivers Influencing Atmospheric Nitrate Transport In Cmentioning
confidence: 99%